An assessment of non‐breeding waterfowl surveys on National Wildlife Refuges in the Central Flyway - Kent Andersson; Craig A. Davis; Grant Harris; David A. Haukos (Wildlife Society Bulletin)
ABSTRACT Many units of the National Wildlife Refuge System (NWRS) in the Central Flyway of the United States were established to conserve and enhance waterfowl populations. Consistent and continuous monitoring of waterfowl abundance on refuges is critical when evaluating the performance of individual refuges as well as the refuge system on a larger scale. It is also essential for providing metrics to determine progress toward established waterfowl use and abundance goals. Despite the considerable resources the U.S. Fish and Wildlife Service spend annually on waterfowl management within the NWRS, the quality of ongoing monitoring efforts outside the breeding season has never been systematically evaluated. We evaluated the quality of historical (1949–2008) waterfowl monitoring data at refuge sites within the Central Flyway during the migration and wintering period (Oct–Mar). Ninety‐six percent of all survey data sets were classified as being of good or fair quality overall. There were, however, some serious issues with the data sets, primarily concerning consistency in survey methodology and temporal survey coverage, as well as lack of coordination among refuges. One‐third of the data sets were collected without the existence of a written survey protocol, creating uncertainty regarding methodological consistency over time. Evaluation of the NWRS's benefits to waterfowl as a whole may be severely hampered by temporally inconsistent survey coverage among and within survey sites. We suggest 7 improvements for future waterfowl surveys that will enhance quality and usability of NWRS survey data. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.